SOSIALISASI PENYELAMATAN PENYU ACEH DI PANTAI SUAK GEUDUBANG ACEH BARAT - Neneng Marlian; Nabil Zurba; Fitria Rahmayanti (Jurnal Marine Kreatif, 2021)
Turtles are marine reptiles that have lived hundreds of millions years ago, where as the  six species turtles from the seven species  turtles,  that exist in the world today are found in Indonesia. However, the continuous hunting and catching of turtles by humans is impacted  to the threat turtle species in the world, including the Aceh’s turtles of  Indonesian.  The implementation on  this activity was a service to the community,  which purpused to increasing  public awareness in order to protected and preserved the Aceh’s turtles.  This community service activity was conducted  on October 27 in 2020 at Suak Geudubang Beach, Sama Tiga Sub-district, West Aceh Regency. Socialization targeting  was the coastal community  who lived around in the Suak Geudubang Beach  of Sama Tiga. The method of service  implementation was trough a  lecturing  approach and opening discussion. The Aceh’s turtles  socialization activity provided an explanation of, definitioned, distributioned of turtles habitat, ecologically and economically potential, international conventioned and Indonesian stated  laws that conserved the protecting of turtles, th efforted of conservation Aceh’s turtles, the potential  coast of  Aceh  as locationed for Aceh's turtles, community empowerment as the main actor and spearhead in the efforted of conservation Aceh's turtles. Socialization rescued of Aceh’s turtles has played a role in  increasing public awareness   sustainability in Aceh, especially  on the Suak Geubang Beach, West Aceh.